Impact of Deposition Power and Gas Flow Ratio on the Tribological Properties of Titanium Vanadium Nitride Thin Films - Kamlesh V. Chauhan; Sushant Rawal; Nicky P. Patel; Dattatraya G. Subhedar (Micromachines, 2023)
Magnetron sputtering was used for producing titanium vanadium nitride (TiVN) coatings on brass substrates. In this research, we investigate how changing the sputtering power and nitrogen:argon (N2:Ar) gas ratio affects the structural and tribological properties of TiVN coatings. A scanning electron microscope (SEM) was used to examine TiVN coating surface morphology. Both variants showed a gradual increase in the intensity of the TiVN coatings’ (111) and (222) peaks. The TiVN coatings’ tribological properties were examined using a pin-on-disc tribometer with varying loads, speeds, and sliding distances. The wear rates of TiVN-coated brass pins were in the range of 2.5 × 10−4 to 9.14 × 10−4 mm3/Nm depending on load, sliding distance, and gas ratio variation, when compared to the wear rates of TiVN-coated brass pins deposited at various powers, which ranged from 1.76 × 10−3 to 5.87 × 10−3 mm3/Nm.